1993
DOI: 10.1302/0301-620x.75b4.8331117
|View full text |Cite
|
Sign up to set email alerts
|

Hip disease in adults with Down syndrome

Abstract: The life expectancy of patients with Down syndrome has increased significantly in recent years. Hip abnormalities occur in children with this syndrome but little is known about their natural history in later life. In 65 adults with Down syndrome we found hip abnormalities in 28%, and this was statistically correlated with walking ability. A subgroup of 18 patients was followed by serial examination; this showed that hip instabifity occurred in adulthood and became worse with time. In some patients, hip instabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 9 publications
0
46
1
1
Order By: Relevance
“…49,50,53 Sensory losses are detected in 40 to 80% of individuals, usually related to hearing loss and cataracts, and hip disease can develop in about 28%. 54 Conversely, females with Down syndrome seem to be less likely to develop breast cancer than the general population, which might be influenced by their shortened life expectancy and/or earlier menopause compared with the general population. 55 The neuropathological features of Alzheimer disease are believed to develop in most people with Down syndrome by the age of 40 years, 56 possibly because of an extra copy of the amyloid-β precursor protein (APP) gene located on chromosome 21.…”
Section: Comorbid Disorders and Ageingmentioning
confidence: 99%
“…49,50,53 Sensory losses are detected in 40 to 80% of individuals, usually related to hearing loss and cataracts, and hip disease can develop in about 28%. 54 Conversely, females with Down syndrome seem to be less likely to develop breast cancer than the general population, which might be influenced by their shortened life expectancy and/or earlier menopause compared with the general population. 55 The neuropathological features of Alzheimer disease are believed to develop in most people with Down syndrome by the age of 40 years, 56 possibly because of an extra copy of the amyloid-β precursor protein (APP) gene located on chromosome 21.…”
Section: Comorbid Disorders and Ageingmentioning
confidence: 99%
“…Age-related disorders also begin earlier in Down syndrome than in the general population. Adults with Down syndrome are at increased risk for skin and hair changes, early-onset menopause, visual and hearing losses,[12] adult-onset seizure disorder,[13] thyroid dysfunction,[14] diabetes,[15] obesity,[16] and musculoskeletal problems [17]. As life expectancy for individuals with Down syndrome has increased in infancy, childhood[18] and adulthood[19], [20] so has the incidence of dementia although development of Alzheimer's dementia is frequent but not inevitable [21]…”
Section: Introductionmentioning
confidence: 99%
“…Their work demonstrated hip abnormality in 7.9% of their patient group, however some report this to be as high as 28% in adult groups. 1 They also noted an increase in acetabular depth, a more horizontal acetabular roof and reduced femoral anteversion. Theoretically these factors would confer an increase in hip joint stability.…”
Section: Discussionmentioning
confidence: 92%
“…Hresko et al demonstrated that hip instability may occur after skeletal maturity and indeed may become worse with time. 1 Given this information, our primary concern was to achieve optimal stability using a suitable prosthesis. We decided against a total hip arthroplasty in view of low patient demand and life expectancy.…”
Section: Discussionmentioning
confidence: 99%